2009
DOI: 10.1007/s00330-009-1621-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MR imaging to assess physiologic variations of myometrial perfusion

Abstract: DCE-MRI is a non-invasive technique that can measure variations of myometrial microcirculation, and thereby be potentially useful to help characterize the role and states of the myometrium in assisted reproductive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 59 publications
4
24
0
Order By: Relevance
“…This notion is important because outer myometrial enhancement, used for enhancement curve analysis for adnexal masses, was demonstrated to be significantly different between post-menopausal women and women of reproductive age with a lower F T , lower Vb, higher PS, higher Ve and lower Dt [11], and thus the appropriateness of using this organ as an internal reference could be discussed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This notion is important because outer myometrial enhancement, used for enhancement curve analysis for adnexal masses, was demonstrated to be significantly different between post-menopausal women and women of reproductive age with a lower F T , lower Vb, higher PS, higher Ve and lower Dt [11], and thus the appropriateness of using this organ as an internal reference could be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…The signal intensity was converted into concentration equivalents assuming a near linear relationship between contrast agent concentration and signal enhancement within the range of 0-3 mM Gd-DOTA values [9]. These data were validated in our laboratory during a previously published study [11] by phantom experiments using the same MR acquisition parameters:…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the improvement of data quality has permitted the application of more complex models, which allow for a separate quantification of the blood flow and the permeability‐surface area (PS). In particular, the two‐compartment exchange model (2CXM) and the adiabatic approximation to the tissue homogeneity model (ATHM) have been shown to be applicable in various clinical and preclinical contexts. It is of great importance to understand the reliability and accuracy of hemodynamic parameter estimates from different models and a number of studies have addressed this issue in the last decade, mostly focusing on the TMs .…”
Section: Introductionmentioning
confidence: 99%
“…Classifi-cation of breast tumors by Brix et al [192] was its first DCE-MRI application. Recently, the 2CXM is gradually becoming popular in various applications, such as brain [193,195,287] and lung cancer [288], myometrium [289], cervix [194] and bladder cancer [290], head and neck tumors [291], and carotid atherosclerotic plaques [191].…”
Section: Clinical Applications Of Parametric Modelsmentioning
confidence: 99%